Angiogenesis and EMT regulators in the tumor microenvironment in lung cancer and immunotherapy - Yan, Taotao; Shi, Jiahai (Frontiers in Immunology, 2024)
Lung cancer remains the primary cause of cancer-related mortality, with factors such as postoperative tumor recurrence, metastasis, and therapeutic drug resistance exacerbating patient outcomes. Immunotherapy has emerged as a transformative approach, challenging conventional treatment paradigms for lung cancer. Consequently, advancing research in lung cancer immunotherapy is imperative. Recent studies indicate that numerous regulators within the tumor microenvironment (TME) drive tumor angiogenesis and epithelial-mesenchymal transition (EMT); these processes are interdependent, reciprocal, and collectively contribute to tumor progression. Tumor angiogenesis not only supplies adequate oxygen and nutrients for cellular proliferation but also establishes pathways facilitating tumor metastasis and creating hypoxic regions that foster drug resistance. Concurrently, EMT enhances metastatic potential and reinforces drug-resistance genes within tumor cells, creating a reciprocal relationship with angiogenesis. This interplay ultimately results in tumor invasion, metastasis, and therapeutic resistance. This paper reviews key regulators of angiogenesis and EMT, examining their impact on lung cancer immunotherapy and progression, and investigates whether newly identified regulators could influence lung cancer treatment, thus offering valuable insights for developing future therapeutic strategies.